Partial replacement of broom sorghum panicle residue and tallow with whole cottonseed in growing-finishing diets for lambs - Urías-Estrada, Jesús David; Estrada-Angulo, Alfredo; Castro-Pérez, Beatriz Isabel; Plascencia, Alejandro; Perea-Domínguez, Xiomara Patricia; Barreras, Alberto; Corona-Gochi, Luis; Zinn, Richard Avery (Journal of the Hellenic Veterinary Medical Society, 2022)
Sixty-four Pelibuey × Katahdin male lambs (14.3± 2.2 kg initial live weight) were used in an 84-d growing-finishing trial to evaluate optimal levels of inclusion of whole cottonseed (WCS) in a broom sorghum panicle residue-based diet. Dietary treatments consisted in partial replacement of broom sorghum panicle residue (SPR) and tallow with 0, 10, 20 or 30% WCS. Control diet contained 66.5% PSR and 3% tallow, and replacing were as follows: 10% of WCS replaced 9% SPR and 1% tallow (WCS10), 20% WCS replaced 18 SPR and 2% tallow (WCS20), and 30% WCS replaced 27% SPR and 3% tallow (WCS30). Inclusion of WCS increased (quadratic component, P=0.03) average daily gain (ADG), dry matter intake (DMI) and gain efficiency. However, with increasing level of WCS substitution the observed/expected dietary net energy ratio decreased (linear effect, P<0.01). The estimated NEm value for WCS determining by the replacement technique at the 10, 20 and 30% levels of inclusion were 2.48, 2.23, and 2.15 Mcal/kg, respectively. Consistent with the increased final weight, hot carcass weight and longissimus muscle area were increased (linear effect, P≤0.03) with increasing level of WCS inclusion. While, dressing percentage and fat thickness tended to increase (linear effect, P=0.10) with increasing WCS level. The partially replacement of broom sorghum panicle residue and tallow by up to 20% inclusion of WCS in finishing diets for lambs enhances ADG, gain efficiency, carcass weight, and LM area. However, the net energy value of WCS decreases with level of inclusion greater than 10%.